Subjective cognitive decline and elder mistreatment in Mexican community-dwelling older adults. (January 2021) - Piña-Escudero, Stefanie Danielle; Chodos, Anna; Weinstein, Cindy A.; Allen, Isabel Elaine; Ávila-Funes, José Alberto; Ritchie, Christine
Highlights: The relationship between cognition and elder mistreatment is understudied in Latin American Countries. There is an Association between subjective cognitive decline and elder mistreatment in community-dwelling Mexican older adults. Our findings pose the hypothesis that elder mistreatment could be acting as a stressor that might have a detrimental effect on cognition. Abstract: Background and objectives: Elder mistreatment in individuals with subjective cognitive decline is an understudied public health problem that violates human rights. Design and Methods: Cross-sectional study of 386 Mexican community-dwelling older adults. Individuals with episodic memory, executive function, language, visuospatial skills or attention cognitive complaints without low cognitive performance scores in the Mini-Mental State Examination and the Isaacs Set Test that were considered positive for subjective cognitive decline (SCD). Elder mistreatment (EM) was considered positive if any of the questions on the Geriatric Mistreatment Scale were answered affirmatively. Logistic regression models were created to test the association between SCD and EM. Results: After adjustments made by age, sex, education and depressive symptoms a positive association was found between SCD and EM (OR = 2.226; 95%CI = 1.296 to 3.822 ; p = 0.004). This association was observed in all subtypes of cognitive complaints except excecutive function: episodic memory (OR = 2.219 ; 95%CI = 1.321 to 3.728 ; p = 0.003), language (OR = 2.500 ; 95% CI = 1.422 to 4.396 ; p = 0.001), visuospatial (OR = 2.158 ; 95%CI = 1.162 to 4.007 ; p = 0.015), attention (OR = 2.197 ; 95%CI = 1.206 to 4.001 ; p = 0.010) and executive (OR = 1 2.062 ; 95%CI = 0.981 to 4.333 ; p = 0.056). Discussion and Implications: This study brings to light the relation between SCD and EM in a population where it has been understudied. Exploring mistreatment in older adults who experience subjective cognitive decline might help preserve their safety and create future prevention and intervention strategies.